The implications of the biomedical model on indigenous health - Unser-Doering, Abrinna (My University, 2019)
The biomedical model focuses solely on biological causes with regards to illness and disease. Adopting this model when investigating the alarmingly high levels of diabetes among Indigenous peoples in Canada points to a genetic predisposition or a biological cause. However, this perspective acts as blinders to the real culprit of the diabetes epidemic: colonization, assimilation, prejudice, racism, and cultural genocide. Interdisciplinary Dialogue Project.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: biomedical models; health; indigenous peoples